A polypropylene composition and its preparation method and application
By using a composite filler of nano-hollow barium sulfate and hollow glass microbeads in the polypropylene composition, the problem of uneven distribution of hollow glass microbeads in the polypropylene material is solved, and the impact strength and appearance quality are improved.
Patent Information
- Application Number
- CN202311620821.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-30
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-11-30
AI Technical Summary
The insulating glass microbeads are unevenly distributed in polypropylene materials, resulting in poor impact resistance and defects in appearance when injection molded into large parts.
A composite filler of nano hollow barium sulfate and hollow glass microbeads is added to the polypropylene composition through a combination of a specific mass ratio to improve impact strength and appearance quality.
While maintaining the overall density is not large, the impact resistance of the polypropylene composition is significantly improved, and the large automotive parts obtained by injection molding are smooth and do not have pits and have a good appearance.
Smart Images

Figure BDA0004579242400000011 
Figure BDA0004579242400000021 
Figure BDA0004579242400000061
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and more specifically to a polypropylene composition, a preparation method and application thereof. Background Art
[0002] With the rapid development of the automobile industry in recent years, lightweight, quality, energy saving, environmental protection, and functionality have become the main goals of the current automobile industry. Polypropylene, as a general engineering plastic, has the characteristics of low price, light weight, solvent resistance, easy recycling, and non-toxicity. It is one of the important lightweight materials for automobiles.
[0003] In order to significantly reduce the density of the overall material and reduce the weight of the material, hollow glass microspheres can be added to the polypropylene material to achieve this, such as the Chinese patent named "A high-rigidity, low-density, low-shrinkage modified polypropylene material and its preparation method". However, the hollow glass microspheres have a certain degree of uneven particle size distribution. On the one hand, the larger hollow glass microspheres are more likely to sink to the bottom during the resin mixing process. On the other hand, the hollow glass microspheres of different particle sizes have different fluidity. The two reasons lead to uneven distribution of hollow glass microspheres in the polypropylene material, thereby reducing the impact resistance of the injection molded product. At the same time, it will also cause pitting on the surface of the polypropylene material when it is injected into a large piece, affecting the appearance.
[0004] Therefore, it is necessary to solve the problems of poor impact resistance of polypropylene materials with hollow glass microspheres as fillers and appearance defects when injection molded into large parts. Summary of the invention
[0005] The primary purpose of the present invention is to provide a polypropylene composition to overcome the problems of poor impact resistance and appearance defects when injection molded into large parts of polypropylene materials using hollow glass microspheres as fillers in the current technology.
[0006] A further object of the present invention is to provide a method for preparing the above polypropylene composition.
[0007] A further object of the present invention is to provide use of the polypropylene composition in the preparation of automobile bumpers.
[0008] The above-mentioned object of the present invention is achieved by the following technical solutions:
[0009] A polypropylene composition comprising the following components in parts by weight:
[0010]
[0011]
[0012] The composite filler includes nano hollow barium sulfate and hollow glass particles in a mass ratio of 1:(1.2-2.5); the mass ratio of nano hollow barium sulfate and hollow glass particles can specifically be 1:1.2, 1:1.5, 1:1.8, 1:2.0, 1:2.3 or 1:2.5.
[0013] The inventor of the present invention has found through research that adding a composite filler obtained by compounding nano hollow barium sulfate and hollow glass microspheres in a specific mass ratio to a polypropylene composition can effectively improve its impact strength while keeping the overall density of the polypropylene composition small. The reason is: on the one hand, the nano hollow barium sulfate has a nano-scale size and a hollow structure, and has a high specific surface area, which can provide more interface areas, thereby better interacting with the polypropylene resin; on the other hand, the different size characteristics of the nano hollow barium sulfate and the hollow glass microspheres can achieve a size matching effect between the fillers and avoid the aggregation and accumulation of the fillers. The combined effect of the two aspects can effectively improve the impact strength of the polypropylene composition and keep the overall density of the polypropylene composition within a lower range. At the same time, the polypropylene composition is injection molded into a large automobile part, and the surface is smooth and shiny with good appearance without pitting. The reasons may be: the size matching effect between the composite fillers and the reduction of the aggregation and accumulation of the fillers, and the coordination with the compatibilizer and the lubricant make the filler dispersed more evenly in the polypropylene composition, and can effectively improve the processing performance and melt fluidity of the polypropylene composition, thereby reducing the occurrence of surface defects.
[0014] In addition, the inventors of the present invention have also found that, unlike precipitated barium sulfate, the nano hollow barium sulfate in the composite filler of the present invention can play a nucleation role, thereby reducing the molding shrinkage of the polypropylene composition.
[0015] That is, the polypropylene composition of the present invention has low density, high notched impact strength and low molding shrinkage, and the surface of the large automobile parts obtained by injection molding has no pitting, is smooth and glossy.
[0016] Optionally, the polypropylene resin has a melt flow rate of 4 to 28 g / 10 min measured at 230° C. and 2.16 kg.
[0017] Preferably, the melt flow rate of the polypropylene resin measured at 230° C. and 2.16 kg is 4.8 to 8 g / 10 min. When the polypropylene resin in this melt flow rate range is selected, the notched impact strength of the obtained polypropylene composition is higher.
[0018] The melt flow rate of the polypropylene resin of the present invention may be measured according to ISO 1133-2011.
[0019] Optionally, the particle size D50 of the hollow glass microspheres is 3 to 20 μm.
[0020] In the present invention, the particle size D50 of the hollow glass microspheres can be measured according to ISO 13320-2020.
[0021] Preferably, the particle size D50 of the hollow glass microspheres is 5 to 10 μm. By selecting hollow glass microspheres within this particle size D50 range, the obtained polypropylene composition has higher impact strength and lower molding shrinkage.
[0022] The nano hollow barium sulfate of the present invention can be obtained from the market or can be prepared by oneself; the preparation can be made by referring to patent CN113697838A. Optionally, the preparation method of the nano hollow barium sulfate is as follows: a) adding 1 to 5 parts by weight of hydrochloric acid and 1 to 4 parts by weight of an auxiliary agent to 400 to 700 parts by weight of a barium carbonate slurry to obtain a pre-reaction mixture A, wherein the auxiliary agent is at least one of sodium hexametaphosphate, sodium pyrophosphate or potassium tripolyphosphate; b) adding 100 parts by weight of water to 1 to 3 parts by weight of a sodium hexametaphosphate solution to obtain a pre-reaction mixture B; c) adding sulfuric acid solution to the pre-reaction mixture A and the pre-reaction mixture B at the same time, reacting at a pH of 1.5 to 1.8 for more than 30 minutes, and then adjusting the pH to 7 to 9 to terminate the reaction; d) filtering by pressure, washing with water, and drying to obtain the nano hollow barium sulfate.
[0023] Typically, the average particle size of the nano hollow barium sulfate is 50 to 500 nm.
[0024] Preferably, the average particle size of the nano hollow barium sulfate is 100-130 nm.
[0025] More preferably, the average particle size of the nano hollow barium sulfate is 120-130 nm. By regulating the average particle size of the nano hollow barium sulfate within this range, the obtained polypropylene composition has higher impact strength and lower molding shrinkage.
[0026] Preferably, the nano hollow barium sulfate is nano hollow barium sulfate whose surface is modified by a silane coupling agent.
[0027] By selecting nano hollow barium sulfate whose surface is modified by a silane coupling agent, the obtained polypropylene composition has higher notched impact strength and lower molding shrinkage.
[0028] The preparation process of the nano hollow barium sulfate with the surface modified by the silane coupling agent is as follows: slurrying the nano hollow barium sulfate, adding the silane coupling agent, adjusting the pH to 3.5-4.0, stirring for 10-20 minutes, dehydrating and drying to obtain the nano hollow barium sulfate with the surface modified by the silane coupling agent; wherein the mass ratio of the nano hollow barium sulfate to the silane coupling agent is 1:(0.3-0.6).
[0029] Optionally, the compatibilizer is at least one of styrene-anhydride-butadiene copolymer (SMA), methyl methacrylate-butadiene-styrene copolymer (MBS), acrylonitrile-butadiene-styrene-acrylate copolymer (ASA), maleic anhydride grafted polypropylene or maleic anhydride grafted ethylene-octene copolymer.
[0030] Preferably, the compatibilizer is maleic anhydride grafted polypropylene.
[0031] By selecting maleic anhydride grafted polypropylene as a compatibilizer, the obtained polypropylene composition has higher notched impact strength and lower molding shrinkage.
[0032] Generally, the grafting rate of maleic anhydride in the maleic anhydride grafted polypropylene is 0.9-1.15%.
[0033] The grafting rate of maleic anhydride of the maleic anhydride grafted polypropylene can be measured by acid-base titration. The specific test process is: dissolve the sample in xylene, and then titrate with potassium hydroxide methanol solution. The calculation formula of the grafting rate is: GD=98.06(V2-V1)C / 2000m×100%; where: GD is the grafting rate, %; C is the concentration of potassium hydroxide methanol solution, mol / L; V2 is the amount of potassium hydroxide methanol solution used for titrating the sample, mL; V1 is the amount of potassium hydroxide methanol solution used for titrating the blank sample, mL; m is the mass of the titrated sample, g.
[0034] Optionally, the lubricant is at least one of graphite oxide, calcium stearate, mineral white oil or erucamide.
[0035] Preferably, the lubricant is graphite oxide.
[0036] Choosing a suitable lubricant is more conducive to improving the processing performance and appearance quality of the composition. The special layered structure of graphite oxide can play a role in lubrication, dispersion and pitting reduction. It also has excellent thermal conductivity, which can effectively transfer the heat of the melt to the mold surface, thereby improving the cooling speed and cooling uniformity of the injection molded parts, and further reducing the defects such as bubbles and shrinkage holes that may be generated in the composition, making the finished injection molding have fewer defects and better impact resistance.
[0037] By using graphite oxide as a lubricant, the obtained polypropylene composition has higher notched impact strength and lower molding shrinkage.
[0038] Optionally, the other auxiliary agent is at least one of an antioxidant or a UV stabilizer.
[0039] Preferably, the antioxidant is a composite antioxidant composed of a primary antioxidant and an auxiliary antioxidant in a mass ratio of 1:(0.5-1).
[0040] Optionally, the primary antioxidant is a phenolic antioxidant, including but not limited to at least one of alkylene bisphenols, polyphenols, hindered phenol-substituted esters, and triazine hindered phenols.
[0041] Optionally, the auxiliary antioxidant is a phosphite antioxidant, including but not limited to at least one of poly(dipropylene glycol) phenyl phosphite, dipropylene glycol bisphosphite, and trioctyl phosphite.
[0042] Optionally, the UV stabilizer includes at least one of derivatives of compounds such as, but not limited to, benzophenone, benzotriazole and salicylate.
[0043] The preparation method of the polypropylene composition comprises the following steps: mixing polypropylene resin, compatibilizer and lubricant to obtain a first premix; mixing the remaining components to obtain a second premix; melt blending the first premix and the second premix, extruding and granulating to obtain the polypropylene composition.
[0044] Typically, the melting temperature is 200-240°C.
[0045] The use of the above polypropylene composition in the preparation of automobile bumpers is also within the protection scope of the present invention.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] The polypropylene composition of the invention has low density, high notched impact strength and low molding shrinkage, and the surface of the large automobile parts obtained by injection molding has no pitting and is smooth and glossy. DETAILED DESCRIPTION
[0048] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.
[0049] Some of the reagents selected in the embodiments and comparative examples of the present invention are described as follows:
[0050] Polypropylene resin 1#: T30S, Lanzhou Petrochemical, melt flow rate 4.8g / 10min;
[0051] Polypropylene resin 2#: Z30S, Maoming Petrochemical, melt flow rate 25g / 10min;
[0052] Polypropylene resin 3#: STM866, Li Changrong Chemical, melt flow rate 8g / 10min;
[0053] Hollow glass microsphere 1#: HM-10, Zhengzhou Shenglait, particle size D50 is 5μm,
[0054] Hollow glass microsphere 2#: HM-15, Zhengzhou Shenglaite, particle size D50 is 10μm,
[0055] Hollow glass microsphere 3#: HM-30, Zhengzhou Shenglaite, particle size D50 is 20μm,
[0056] Nano hollow barium sulfate 1#, homemade, preparation method is as follows:
[0057] 1) adding 100 parts by mass of nano-barium carbonate into 400 parts by mass of water and mixing to obtain nano-barium carbonate slurry, adding 1 part by mass of 31% hydrochloric acid and 1.5 parts by mass of an auxiliary agent to the barium carbonate slurry, and mixing thoroughly to obtain a pre-reaction mixture A, wherein the auxiliary agent consists of sodium hexametaphosphate, sodium pyrophosphate, and potassium tripolyphosphate, wherein the mass ratio of sodium hexametaphosphate: sodium pyrophosphate: potassium tripolyphosphate is 4.5:1.5:2;
[0058] 2) adding 2 parts by mass of sodium hexametaphosphate to 100 parts by mass of water to prepare a sodium hexametaphosphate solution, and then adding 1 part by mass of 31% hydrochloric acid to obtain a pre-reaction mixture B;
[0059] 3) adding the pre-reaction mixture A and the pre-reaction mixture B to the sulfuric acid solution at the same time, and stabilizing the pH value at 3 during the addition; after all are mixed, the pH value is 1.5; the sulfuric acid solution is prepared by 50 parts by mass of 98% concentrated sulfuric acid and 300 parts by mass of water;
[0060] 4) fully stirring the mixture obtained in step 3) for more than 30 minutes, and adjusting the pH to 8 to terminate the reaction;
[0061] 5) After filter pressing, water washing and drying, nano hollow barium sulfate 1# is obtained, and its average particle size is 120 nm.
[0062] Nano hollow barium sulfate 2# is self-made, and the preparation method is basically the same as that of nano hollow barium sulfate 1#, except that: in step 1), the amount of nano barium carbonate is 80 parts by weight, the amount of 31% hydrochloric acid is 3 parts by weight, and the amount of auxiliary agent is 2.5 parts by weight. The average particle size of the nano hollow barium sulfate 2# obtained finally is 100nm (measured by Malvern laser particle size analyzer, the same below).
[0063] Nano hollow barium sulfate 3# is self-made. The preparation method is basically the same as that of nano hollow barium sulfate 1#, except that in step 1), the amount of nano barium carbonate is 140 parts by weight, the amount of 31% hydrochloric acid is 5 parts by weight, and the amount of auxiliary agent is 4 parts by weight. The average particle size of the nano hollow barium sulfate 3# obtained is 130nm.
[0064] Nano hollow barium sulfate 4# is self-made. The preparation method is basically the same as that of nano hollow barium sulfate 1#, except that in step 1), the amount of nano barium carbonate is 260 parts by weight, the amount of 31% hydrochloric acid is 3 parts by weight, and the amount of auxiliary agent is 2 parts by weight. The average particle size of the nano hollow barium sulfate 4# obtained is 450nm.
[0065] Nano hollow barium sulfate 5#: Take 2 parts by mass of nano hollow barium sulfate 1#, slurry it, add 1 part by mass of silane coupling agent (γ-aminopropyltriethoxysilane, Yunsheng Chemical, KH550), adjust the pH to 4, stir for 1 hour, dehydrate and dry, and obtain nano hollow barium sulfate 5#.
[0066] Ordinary barium sulfate: Dongguan Zhenming Chemical, precipitated barium sulfate;
[0067] Composite fillers 1 to 13# are homemade, and the preparation process is as follows: according to the formula in Table 1, mix the components to obtain the composite fillers.
[0068] Table 1 Composite filler formulation (parts by weight)
[0069]
[0070]
[0071] Lubricant 1#: graphite oxide, Shanghai Zhenzhun Biological;
[0072] Lubricant 2#: erucamide, Lion;
[0073] Compatibilizer 1#: Maleic anhydride grafted polypropylene, B2, Coase;
[0074] Compatibilizer 2#: Maleic anhydride grafted POE, W1A, Kerida;
[0075] Antioxidant: prepared by mixing antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; wherein antioxidant 1010 and antioxidant 168 are both commercially available products;
[0076] UV stabilizer: UV-326, commercially available.
[0077] Unless otherwise specified, the components (eg antioxidant, UV stabilizer) used in the parallel examples and comparative examples are all the same commercially available products.
[0078] The properties of the polypropylene compositions provided in the embodiments and comparative examples of the present invention were measured according to the following test methods:
[0079] (1) Surface inspection of large injection molded parts: The polypropylene compositions prepared in the embodiments and comparative examples were used to respectively mold large automobile bumper parts, and the surface conditions of the injection molded parts were observed; the injection molded parts with smooth surfaces and no pitting were recorded as level 1; the injection molded parts with smooth surfaces and pitting, with 1 to 5 pitting within 10 cm*10 cm, were recorded as level 2; the injection molded parts with smooth surfaces and pitting, with 6 to 10 pitting within 10 cm*10 cm, were recorded as level 3. Generally speaking, the surface condition of the injection molded parts is required to be level 1 to meet the application requirements.
[0080] (2) Tensile strength: tested in accordance with ISO 527-2-2016, with a tensile speed of 50 mm / min;
[0081] (3) Izod notched impact strength: tested in accordance with ISO180-2000 standard;
[0082] (4) Molding shrinkage: Molding shrinkage: Tested in accordance with GB / T17037.4-2003, it refers to the dimensional difference between the dry sample and the mold cavity that molded it, measured at laboratory temperature within 16 to 24 hours after the sample is molded. The sample is a small square piece of 60×60×2 mm. The length l1 and width b1 of the test sample and the length l0 and width b0 of the mold cavity are tested. The molding shrinkage SMp parallel to the melt flow direction is measured at the middle of the sample width; the molding shrinkage SMn perpendicular to the melt flow direction is measured at the middle of the sample length. The calculation formula is: SMp=100(l0-l1) / l0 and SMn=100(b0-b1) / b0. The average of the two is then taken to obtain the molding shrinkage.
[0083] (5) Density: tested in accordance with ASTM D792 standard.
[0084] The polypropylene compositions of the embodiments of the present invention and the comparative examples are prepared by the following preparation method:
[0085] Weigh each component according to the formula; mix polypropylene, compatibilizer (if any), and lubricant (if any) to obtain a first premix; mix the remaining components (components other than polypropylene, compatibilizer, and lubricant) to obtain a second premix; then mix the first premix and the second premix evenly and add them into a twin-screw extruder, and obtain a polypropylene composition through melt blending and extrusion granulation (the extrusion temperature of the twin-screw extruder is 200-240°C: 200°C for the first section, 240°C for the second to fourth sections, 220°C for the fifth to eighth sections, and 240°C for the ninth section of the die head).
[0086] Examples 1 to 16
[0087] Examples 1 to 16 provide a series of polypropylene compositions, whose formulations are shown in Tables 2 and 3.
[0088] Table 2 Formulas of Examples 1 to 7 (parts by weight)
[0089]
[0090] Table 3 Formulas of Examples 8 to 16 (parts by weight)
[0091]
[0092]
[0093] Comparative Examples 1 to 8
[0094] Comparative Examples 1 to 8 provide a series of polypropylene compositions, whose formulations are shown in Table 4.
[0095] Table 4 Formulas of Comparative Examples 1 to 8 (parts by weight)
[0096]
[0097] The properties of the polypropylene compositions of the embodiments and comparative examples were measured according to the above-mentioned test methods. The test results are shown in Table 5.
[0098] Table 5 Performance test results of polypropylene compositions of various embodiments and comparative examples
[0099]
[0100] From Table 5, we can see that:
[0101] By matching the components and their amounts, the density of the polypropylene compositions of Examples 1 to 16 is 1 g / cm 3 Below, the notched impact strength is higher than 13KJ / m 2 , the molding shrinkage is lower than 0.52%, and the surface test results of the large injection molded parts all reach level 1, indicating that the polypropylene composition of the present invention has low density, high notch impact strength and low molding shrinkage, and the surface of the large automobile parts obtained by injection molding has no pitting, smooth and shiny. In addition, the tensile strength of the polypropylene composition of the present invention is above 30MPa, which meets the requirements of conventional application scenarios.
[0102] In Comparative Example 1, no composite filler is added, and the notched impact strength of the polypropylene composition is low and the shrinkage rate is high. In Comparative Example 2, the barium sulfate in the composite filler is precipitated barium sulfate, and the notched impact strength of the polypropylene composition is poor, the density is high, the shrinkage rate is high, and the surface detection of the large automobile parts obtained by injection molding is poor. The mass ratio of the composite fillers added in Comparative Examples 3 and 4 is not appropriate, and the surface detection of the large automobile parts obtained by injection molding of the polypropylene composition is poor, among which the notched impact strength of the polypropylene composition in Comparative Example 4 is poor and the molding shrinkage rate is high. The fillers in Comparative Example 5 are all hollow glass microbeads, the notched impact strength of the polypropylene composition is low and the molding shrinkage rate is high, and the surface detection of the large automobile parts obtained by injection molding is poor. The fillers in Comparative Example 6 are all nano hollow barium sulfate, and the surface detection of the large automobile parts obtained by injection molding of the polypropylene composition is poor. In Comparative Example 7, no lubricant is added, the notched impact strength of the polypropylene composition is poor, and the surface detection of the large automobile parts obtained by injection molding is poor. In Comparative Example 8, no compatibilizer is added, the notched impact strength of the polypropylene composition is low, and the surface detection of the large automobile parts obtained by injection molding is poor.
[0103] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A polypropylene composition, characterized in that The composition comprises the following components in parts by weight: Polypropylene resin 65~72 parts, 15~35 parts of composite filler, Compatibilizer 2.5~5 parts, 1~4 parts of lubricant, Other additives 0~5 parts; The composite filler comprises nano hollow barium sulfate and hollow glass microspheres in a mass ratio of 1:(1.2-2.5); The particle size D50 of the hollow glass microspheres is 3-20 μm; The average particle size of the nano hollow barium sulfate is 50-500 nm.
2. The polypropylene composition according to claim 1, characterized in that The melt flow rate of the polypropylene resin measured at 230° C. and 2.16 kg is 4-28 g / 10 min.
3. The polypropylene composition according to claim 1, characterized in that: The nano hollow barium sulfate is a nano hollow barium sulfate with its surface modified by a silane coupling agent.
4. The polypropylene composition according to claim 1, characterized in that: The compatibilizer is at least one of styrene-anhydride-butadiene copolymer, methyl methacrylate-butadiene-styrene copolymer, acrylonitrile-butadiene-styrene-acrylate copolymer or maleic anhydride grafted ethylene-octene copolymer.
5. The polypropylene composition according to claim 1, characterized in that: The lubricant is at least one of graphite oxide, calcium stearate, mineral white oil or erucamide.
6. The polypropylene composition according to claim 1, characterized in that: The other auxiliary agent is at least one of an antioxidant or a UV stabilizer.
7. The method for preparing the polypropylene composition according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: mixing polypropylene resin, compatibilizer and lubricant to obtain a first premix; mixing the remaining components to obtain a second premix; and melt-blending the first premix and the second premix, extruding and granulating to obtain the polypropylene composition.
8. Use of the polypropylene composition according to any one of claims 1 to 6 in the preparation of automobile bumpers.
Citation Information
Patent Citations
Preparation method of spherical hollow nano barium sulfate
CN113697838A
Lightweight, scratch-resistant and compression-resistant polypropylene composite material and preparation method thereof
CN109735007A
Energy-saving high-gloss flame-retardant polypropylene composite material special for intelligent closestool and preparation method thereof
CN111793275A